SalA Attenuates Ischemia/Reperfusion-Induced Endothelial Barrier Dysfunction via Down-Regulation of VLDL Receptor Expression - Dan Yang; Peng Zhang; Tingfeng Wang; Lili Gao; Zhengdong Qiao; Yongjun Liang; Bo Yu (Cellular Physiology and Biochemistry, 2014)
Background: Salvianolic acid A (SalA) has been shown to confer robust protection against endothelial injury. VLDL receptor is expressed at high levels on the endothelial surface, however its biological effect on endothelial cells has not yet been completely elucidated. Here, we investigated molecular effects of SalA on endothelial VLDL expression and barrier dysfunction under conditions of ischemia/reperfusion (IS/RP). Methods: Human umbilical vein endothelial cells (HUVECs) treated with SalA were subjected to IS/RP stimulation. Endothelial permeability, ZO-1 distribution, actin cytoskeleton reorganization, and intracellular reactive oxygen species (ROS) generation were examined. The mRNA levels were tested by real-time RT-PCR and the protein levels were determined by immunoblot analysis. Results: Pretreatment of HUVECs with SalA markedly attenuated IS/RP-induced endothelial hyperpermeability, discontinuous ZO-1 staining, actin stress fiber formation, and intracellular ROS generation. IS/RP activated p38 MAPK signaling and enhanced VLDL receptor expression, and inactivation of p38 MAPK abolished increase of VLDL receptor expression. Furthermore, siRNA experiments showed that VLDL receptor was a crucial mediator of endothelial barrier dysfunction and intracellular ROS generation induced by IS/RP. Importantly, SalA effectively suppressed IS/RP-induced activation of p38 MAPK signaling and increase of VLDL receptor expression. Conclusion: These results for the first time demonstrated that SalA protected against IS/RP-induced endothelial barrier dysfunction through suppression of VLDL receptor expression.